Markers for work disability in anti-neutrophil cytoplasmic antibody-associated vasculitis. - LITTLE, MARK (My University, 2014)
Objectives. ANCA-associated vasculitis (AAV) commonly affects those of working age. Since survival rates have been transformed by immunotherapeutics, the measurement of other outcomes has become increasingly relevant. Work disability is an important outcome for both patient and society that has yet to be fully evaluated in AAV. We aimed to assess employment status in AAV patients and identify putative predictors of their work disability. Methods. A cross-sectional study was undertaken. AAV cases were recruited according to consecutive clinic attendance. Subjects completed a questionnaire that determined employment status and other psychosocial measures. Clinical factors were concurrently recorded by the attending physician. From the data of those subjects of working age, a multivariable model was developed using forward stepwise logistic regression to identify the independent associations of work disability, defined by those subjects reporting unemployment secondary to ill-health. Results are expressed as odds ratios (ORs) and 95% CIs. Results. Of the 410 participants (84.4% response rate), 149 (36.7%) were employed, 197 (48.6%) retired and 54 (13.3%) unemployed secondary to ill health. Of those of working age, 26.0% were considered work disabled. Fatigue (OR 7.1, 95% CI 1.5, 33.1), depression (OR 4.4, 95% CI 1.8, 10.8), severe disease damage [Vasculitis Damage Index (VDI) > 4 (OR 3.9, 95% CI 1.01, 14.7)] and being overweight (OR 3.4, 95% CI 1.3, 8.9) were independently associated with their unemployment. Conclusion. A quarter of working-age AAV subjects reported unemployment as a result of ill health and are characterized by high levels of fatigue, depression, disease damage and being overweight. These potentially modifiable factors may inform future multidisciplinary interventions aimed at alleviating work disability.
PUBLISHED
Keywords: overweight; overweight